Identification of genes encoding Nuclear factor-YB in cassava (Manihot esculenta Crantz) using bioinformatics - Duc Ha, Chu; Thi Thao, Le; Quynh Mai, Le; Thi Ly Thu, Pham (VNU Journal of Science: Natural Sciences and Technology, 2017)
Nuclear factor-Y (NF-Y) transcription factor can be found in most of plant species and is known to play important role in plant growth, development and stress response. In this study, 17 genes encoding NF-YB subunit were identified in cassava ( Manihot esculenta Crantz). These genes were located in chromosomes with an uneven ratio. Analysis of gene structure indicated that MeNF-YB genes were varied in length and exon/intron organization. Genes in the same clade shared similar exon/intron structure. Based on available microarray database, most of NF-YB genes were up-regulated in at least 1 major tissue. Interestingly, MeNF-YB12 was highly expressed in shoot apical meristem, while MeNF-YB2 was specifically accumulated in friable embryogenesis callus. Additionally, some genes, such as MeNF-YB4/8/13/5 were found to be strongly expressed in friable embryogenesis callus. Our results strongly indicated that NF-YB genes in cassava might be associated with various growth and developmental processes in meristem tissues.